Degradation of Softwood, Hardwood, and Grass Lignocelluloses by Two Streptomyces Strains - Antai, Sylvester P. (1981)
Two Streptomyces strains, S. viridosporus T7A and S. setonii 75Vi2, were grown on softwood, hardwood, and grass lignocelluloses, and lignocellulose decomposition was followed by monitoring substrate weight loss, lignin loss, and carbohydrate loss over time. Results showed that both Streptomyces strains substantially degraded both the lignin and the carbohydrate components of each lignocellulose; however, these actinomycetes were more efficient decomposers of grass lignocelluloses than of hardwood or softwood lignocelluloses. In particular, these Streptomyces strains were more efficient decomposers of grass lignins than of hardwood or softwood lignins.